Influence of husbandry conditions on animal welfare at cattle farms in Turkey - Koseman, Abdurrahman; Seker, Ibrahim (Polska Akad Nauk, Inst Genetyki I Hodowli Zwierzat, 2019)
The aim of this study was to analyse husbandry conditions in terms of their impact on animal welfare at beef and dairy cattle farms and the perceptions of cattle producers in the Malatya province of Turkey. A total of 172 cattle farms altogether rearing about 12 thousand cattle were investigated in three administrative districts with the highest numbers of farms in the province, selected using a random ised sampling method. The survey forms developed by the Agriculture and Rural Development Supporting Agency [ARDSA 2015] were used in this study. Volunteer-based face-to-face interviews were conducted with these breeders. Additionally, farms were visited to evaluate the suitability of their livestock husbandry conditions. The statistical analysis included the counts and percentage frequencies (%) measured for each question answered in the survey. Husbandry and housing conditions in cattle farms were observed to be insufficient with regard to sonic of the parameters evaluated. To solve the identified problems, priority should he given to the education of farm workers, official control and surveillance operations should be established, while the adaptation of farms to ensure optimal animal management conditions should be considered as an important criterion in animal support programmes.
Keywords: animal welfare; cattle husbandry; livestock farming